2010
DOI: 10.1007/bf03219776
|View full text |Cite
|
Sign up to set email alerts
|

Measuring middle school students’ interest in statistical literacy

Abstract: The following paper describes the development of an instrument designed to assess middle school students' interest in statistical literacy. The paper commences with a review of the literature as it relates to interest in this context and then proposes a theoretical model upon which the proposed instrument is based. The Rasch Rating Scale model is then applied to student responses to items in the instrument and fit statistics are analysed in order to assess the extent to which these responses conform to the req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
2
13
0
2
Order By: Relevance
“…Considering these explanations, we can say that the Turkish family structure and the collectivist culture are similar, based upon the perspective of the children and individuals' profile features. Thus, our finding is consistent, though it is surprising, and Carmichael, Callingham, Hay and Watson's (2010) study revealed that mathematics interest exhibits a quadratic connection with mathematical self-efficacy, in that those students who have high mathematical self-efficacy are aware that they can do mathematics tasks well, and in consequence will lose attention or interest (Silvia 2003), and many studies' finds (e.g. Pajares & Miller 1994;Güzel 2006) that recommended that students who have a high mathematical selfefficacy demonstrated higher mathematics performances than students who have a low mathematical self-efficacy and vice versa.…”
Section: Discussionsupporting
confidence: 83%
“…Considering these explanations, we can say that the Turkish family structure and the collectivist culture are similar, based upon the perspective of the children and individuals' profile features. Thus, our finding is consistent, though it is surprising, and Carmichael, Callingham, Hay and Watson's (2010) study revealed that mathematics interest exhibits a quadratic connection with mathematical self-efficacy, in that those students who have high mathematical self-efficacy are aware that they can do mathematics tasks well, and in consequence will lose attention or interest (Silvia 2003), and many studies' finds (e.g. Pajares & Miller 1994;Güzel 2006) that recommended that students who have a high mathematical selfefficacy demonstrated higher mathematics performances than students who have a low mathematical self-efficacy and vice versa.…”
Section: Discussionsupporting
confidence: 83%
“…None appeared for more than one year-level pair. In a study of middle school students of the same age as this study, Carmichael and Hay (2009) reported gender differences for males and females on questions relating to the interests they had related to statistical literacy contexts. They found significantly more positive responses for males to three questions that potentially could contribute to better performance on Q5 based on the mean and Q23 on outliers: "I'm interested in working on problems involving data and statistics"; "I'm interested in looking up unusual statistics"; "I'm interested in using averages to compare sports."…”
Section: Discussionmentioning
confidence: 99%
“…Öğretim elemanları da olası hata ve yanılgılara yer vermelerini öğrencilerin yanlış anlam geliştirmelerini önlemek şeklinde gerekçelendirmektedir. Öğrencilerin olası hata ve yanılgıları bilmesi veya farkında olması önemli görülmektedir (Carmichael, Callingham, Watson ve Hay, 2009;Gal, 2002). Ancak bu göstergenin derslerde matematik tabanlı uyarılar etrafında yoğunlaşması kavram yanılgılı durumlara yer verilmesini engellemektedir.…”
Section: Tartışma Ve Sonuçunclassified